Online Shopping Behavior of Fishermen in Popisi Village, Banggai Laut Regency, Central Sulawesi - Sumarto M. Lalu; Safriadi Safriadi; Wahyu Chandra; Jayana Suryana Kembara (CENDERAWASIH: Jurnal Antropologi Papua, 2025)
This study examines the transformation of consumption practices among fishing communities in Popisi Village, Banggai Laut Regency, Central Sulawesi, particularly in relation to the adoption of online shopping platforms. Traditionally characterized by subsistence-oriented livelihoods, limited education, and restricted access to markets, fishermen in Popisi Village are increasingly exposed to digital technologies that reshape their economic and social behavior. Using a descriptive qualitative approach, this research explores patterns of online shopping behavior, types of products purchased, platforms and payment methods used, as well as the motivations underlying these practices. Data were collected through in-depth interviews, participatory observation, and documentation involving twelve informants consisting of fishermen, fishermen’s wives, and individuals directly engaged in online shopping activities. The findings reveal that approximately 35% of fishermen have begun using e-commerce platforms such as Shopee, Tokopedia, and TikTok, primarily to purchase clothing, household goods, electronic items, and fishing equipment that are difficult to obtain locally. Online shopping is generally conducted selectively and situationally, particularly prior to religious holidays or during periods of higher income from fishing activities. Convenience, time efficiency, competitive prices, and access to diverse products emerge as the main motivations driving this behavioral shift. However, this digital adaptation remains constrained by unstable internet connectivity, limited digital literacy, and fluctuating household incomes that influence spending decisions. Overall, the study demonstrates that digitalization has initiated an early-stage transformation of consumption culture within the fishing community, reflecting both adaptive strategies toward modernity and persistent structural challenges. These findings highlight the need for improved digital infrastructure and targeted digital literacy initiatives to ensure that the benefits of e-commerce contribute positively to the long-term welfare and economic sustainability of coastal fishing communities.